Trends in criminal convictions in Japan for vehicle collisions where one driver suffers from an epileptic seizure - Mineko Baba (19774386) (2015)
For the last fourteen years in Japan, casualties due to traffic collisions have decreased. There were 9,073 traffic fatalities in 2000 and 4,113 in 2014. However, it has been argued that traffic collisions caused by one driver’s poor physical condition account for 10% of all traffic collisions. To reduce collisions to an even greater degree, this type of collision should be prevented. To investigate this issue, we studied criminal liability for drivers who caused a collision while having an epileptic seizure while driving. We searched for information on traffic collisions caused by epileptic seizures while driving, and criminal punishments for the epileptic driver. We used databases of five nationwide newspapers (Asahi, Mainichi, Nikkei, Sankei, Yomiuri). We used LEX/DB that is a database of the precedent after 1875 in Japan, too. We studied 27 cases from 1964 to 2014. Twenty drivers were prosecuted, and seven drivers were not. Seventeen of the twenty cases that were tried resulted in convictions, and all of the drivers who were found guilty had been diagnosed with epilepsy before being involved in vehicle collisions. Ten of the drivers found guilty denied criminal liability in arraignment. The sentences rendered appear to have become more severe in recent years. Criticism for vicious vehicle collisions has led to changes in public opinion in Japan, thus the punishments for traffic fatalities and injuries due to a collision became heavier after 2001. Accidents due to chronic diseases—regarded as vicious collisions—are subject to scorn from the public, resulting in harsher penalties. It is necessary for drivers to recognize the risks of having seizures while driving. Furthermore, it is necessary for doctors to give clear instructions to drivers. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.2